Validating At-Home Urinary Hormone Measurements in Postpartum and Perimenopause Fertility Transitions - Thomas P. Bouchard; Patricia K. Doyle-Baker; Paul J. Yong; Richard Fehring; Mary Schneider (Women's Health Reports)
Background: Measuring quantitative menstrual cycle hormones at home may help women better understand their postpartum and perimenopause fertility transitions, but these quantitative fertility monitors require validation. Materials and Methods: This study included 16 North American women, aged 28–51, during either the postpartum (n = 8, cycles = 18) or perimenopause (n = 8, cycles = 35) fertility transitions testing daily first-morning urine testing with both the Mira Monitor and ClearBlue Fertility Monitor (CBFM) along with menstrual cycle parameter tracking. The main outcome measures were a rise in estrone-3-glucuronide (E13G) and luteinizing hormone (LH) urine hormone values from the Mira monitor correlated to low, high, or peak values on the CBFM. Results: Both in the postpartum and perimenopause transitions, the identification of the day of ovulation based on the LH surge on the Mira and CBFM monitors was highly correlated (R = 0.94 and 0.83, p < 0.001). The E13G levels on the Mira monitor were significantly higher for a CBFM reading of “High” compared with “Low” for both the postpartum and perimenopausal cycles (all p < 0.001). Similarly, the LH levels on the Mira monitor were significantly higher for a CBFM reading of “Peak” (LH surge) compared with “High” for both the postpartum and perimenopausal cycles (all p < 0.001). Conclusions: The LH surge and levels of E13G in urine identified on the quantitative Mira fertility monitor strongly correlate to the LH surge and the shift from low to high on the CBFM during the postpartum and perimenopause transitions.